Person-Independent Head Pose Estimation Using Biased Manifold Embedding. (13th February 2008) - Balasubramanian Balasubramanian, Vineeth Nallure Vineeth Nallure; Krishna Krishna, Sreekar Sreekar; Panchanathan Panchanathan, Sethuraman Sethuraman
Abstract : Head pose estimation has been an integral problem in the study of face recognition systems and human-computer interfaces, as part of biometric applications. A fine estimate of the head pose angle is necessary and useful for several face analysis applications. To determine the head pose, face images with varying pose angles can be considered to be lying on a smooth low-dimensional manifold in high-dimensional image feature space. However, when there are face images of multiple individuals with varying pose angles, manifold learning techniques often do not give accurate results. In this work, we propose a framework for a supervised form of manifold learning called Biased Manifold Embedding to obtain improved performance in head pose angle estimation. This framework goes beyond pose estimation, and can be applied to all regression applications. This framework, although formulated for a regression scenario, unifies other supervised approaches to manifold learning that have been proposed so far. Detailed studies of the proposed method are carried out on the FacePix database, which contains 181 face images each of 30 individuals with pose angle variations at a granularity of1 ∘ . Since biometric applications in the real world may not contain this level of granularity in training data, an analysis of the methodology is performed on sparsely sampled data to validate its effectiveness. We obtained up to2 ∘ average pose angle estimation error in the results from our experiments, which matched the best results obtained for head pose estimation using related approaches.